Analisis Penerapan Hukum Keluarga Islam dalam Meningkatkan Harmoni Sosial di Kabupaten Bireuen - M. Nur, Abdullah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2024)
This research aims to analyze the application of Islamic family law in enhancing social harmony in Bireuen District. In a pluralistic society, the role of Islamic family law is crucial in addressing issues that arise in family life, such as divorce, inheritance distribution, and conflicts among family members. The study uses a qualitative approach with a descriptive-analytical method to explore how Islamic family law is applied in Bireuen and its impact on the social harmony of the community. The results show that Islamic family law in Bireuen functions not only as a formal legal instrument but also integrates with local values that emphasize deliberation and social wisdom. The active involvement of the community and the role of religious leaders are key factors in the successful application of this law. This study contributes to the development of a more contextual understanding of the application of Islamic family law with local wisdom and opens opportunities for further research in other regions of Indonesia.